THE EFFORTS OF ISLAMIC RELIGIOUS TEACHERS IN IMPROVING THE ABILITY TO READ THE AL-QUR'AN WRITING IN CLASS IV STUDENTS INPRIMARY SCHOOL - Salmia,; Sudarmin,; A. Muhammad Yusri, (International Journal of Social Science, 2022)
The purpose of this study concerns (1) describing the form of the teacher's efforts in improving the students' reading and writing skills of the Al-Qur'an; (2) after describing the teacher's efforts, it can be seen the factors that are supporting and hindering Islamic religious education teachers in improving Al-Qur'an reading and writing skills. This type of research is descriptive qualitative. Data were collected through interviews, observation, and documentation. This study uses data analysis techniques, consisting of the data collectionstages, data reduction, data presentation, and drawing conclusions, while the validity of the data is done by checking the results of interviews, data sources, and implementation time. The research results conducted by Islamic Religious Education teachers are (1) the efforts of Islamic Religious Education teachers in improving Students' reading and writing skills of the Qur'an are to collaborate with students' parents, create good learning conditions, and conduct learning in a comfortable place. (2) The advantages and disadvantages of improving the reading and writing skills of the Qur'an, the advantages are the cooperation between parents and Islamic Education teachers and the support of the school principal. In contrast, the disadvantages are the lack of facilities and infrastructure such as books that can increase students' interest in learning to write the Qur'an.